THE RIGHT TO LEARNING AS THE TELEOLOGICAL QUALITY OF EDUCATION: FROM THE QUALITY OF LEARNING BEYOND GUARANTEEING ENROLLMENT - de Lisbôa, Wandré (Revista Gênero e Interdisciplinaridade, 2023)
The purpose of this Article is to bring to the discussion that having the Right to Education and/or access to it is not enough; it is necessary to have the right and access to Learning, which constitutes, in the current studies of Human Rights in interface with the Sciences of Education, the main goal of Education and Human Development. It is necessary to undo the classic idea, still perennial and of a place of teaching speech that if there was teaching, there was also Learning. Not necessarily, even though it should be. This Article will defend that this prerogative should be consistent and that people do not learn in series, nor in the same way. For this defense, we bring to the discussion new information about Learning, based on studies on Educational Sciences; about Neuroscience; on Psychology and Psychoanalysis of Learning; and on Linguistics Applied to Education – information all of which are transversal to current, poignant and stimulating studies of Human Rights in Education.